Effects of anaerobic training on physical performance in soccer players: a systematic review - Vega Soniawan; Ikhwanul Arifan (IICET (Indonesian Institute for Counseling, Education and Therapy), 2025)
Soccer is a high-intensity intermittent sport characterized by repeated efforts of sprinting, jumping, and rapid directional changes, demanding highly developed anaerobic capacities. Despite growing scholarly interest in anaerobic training for soccer players, the diversity of training modalities, populations, and outcome measures has precluded definitive conclusions regarding optimal training configurations. This systematic review aimed to synthesize the available scientific evidence on the effects of anaerobic training interventions on physical performance outcomes in soccer players. Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines (Page et al., 2021), a comprehensive search was conducted on the Scopus database, yielding an initial pool of 931 records. After removing 15 duplicate records, 237 records were screened based on title and abstract, of which 174 were excluded. Of the 63 full-text articles assessed for eligibility, 41 were further excluded due to irrelevant study designs, non-intervention nature, or populations outside the scope. Consequently, 22 studies published between 2021 and 2025 were included in the final synthesis. The findings indicate that sprint interval training, plyometric training, and combined anaerobic training programs significantly improve repeated sprint ability, sprint speed, explosive power, and change-of-direction performance in soccer players across various age groups and competitive levels. High-intensity interval training emerges as an effective and versatile approach when individualized according to training frequency, intensity, and recovery parameters. These results have important implications for sports scientists and coaches in designing evidence-based anaerobic conditioning programs. Future research should prioritize female populations, long-term follow-up assessments, and training periodization frameworks.